The Legalization Of Medical Cannabis: A Comparative Approach Of The Thai Narcotics Act B.E.2522 (1979) - Eviera Riza INDRIANI; Abdul MADJID (Indonesia Strategic Sustainability, 2022)
Based on Appendix I, point 8 of Law no. 35 of 2009 concerning Narcotics, Cannabis is classified as Schedule I narcotics. Referring to Article 7 of Law 3 of 2009, narcotics other than Schedule I can be used to benefit health services and the development of science and technology. Meanwhile, narcotics from Schedule I can only be used to develop science and technology. Thus, Cannabis can only be used for the development of science and technology with the permission of the Minister of Health and the recommendation of the Head of the National Agency of Drug and Food Control (BPOM). This study compares favorable laws regarding narcotics, especially Cannabis, which is regulated in the law of Indonesia and Thailand. This study also explores the regulation of Cannabis as an alternative in the future in Indonesia. In normative law research, statutory and comparative approaches compare the Narcotics Laws in Indonesia and Thailand. Cannabis is not included in the Narcotics class that can be used for health since it is classified as Schedule I. On the official website of the Royal Gazette, it was announced that Thailand had legalized the use of Cannabis as a medical alternative. It will be legalized 120 days after the announcement is made.